The Impact of Different Drying Methods on the Metabolomic and Lipidomic Profiles of Arthrospira platensis - Mróz, Marika; Parchem, Karol; Jóźwik, Joanna; Domingues, M Rosário; Kusznierewicz, Barbara (Molecules (Basel, Switzerland), 2024)
Drying is an inseparable part of industrial microalgae production. In this work, the impacts of eight different drying methods on the metabolome and lipidome of Arthrospira platensis were investigated. The studied drying methods were freeze drying (FD), sun drying (SD), air drying at 40 and 75 °C (AD' and AD″), infrared drying at 40 and 75 °C (IRD' and IRD″), and vacuum drying at 40 and 75 °C (VD' and VD″). Results gathered by reversed-phase liquid chromatography separation coupled with high-resolution tandem mass spectrometry with electrospray ionization (RP-LC-ESI-Orbitrap HRMS/MS) analysis allowed researchers to identify a total of 316 metabolites (including lipids) in aqueous and ethanolic extracts. The compounds identified in ethanolic extracts were mainly lipids, such as neutral and polar lipids, chlorophylls and carotenoids, while the compounds identified in the aqueous extracts were mainly amino acids and dipeptides. Among the identified compounds, products of enzymatic and chemical degradation, such as pyropheophytins, monoacylglycerols and lysophosphatidylcholines were also identified and their amounts depended on the drying method. The results showed that except for FD method, recognized as a control, the most protective method was AD'. Contrary to this, VD' and VD″, under the conditions used, promoted the most intense degradation of valuable metabolites.
Keywords: Desiccation; lipidy; mikrořasy; metabolomika; Metabolomics; metabolom; vysoušení; drying; lipidomics; HPLC-HRMS/MS; Lipids; Metabolome; microalgae; Lipidomics; Tandem Mass Spectrometry; Arthrospira platensis; metabolomics; lyofilizace; tandemová hmotnostní spektrometrie; Microalgae; Spirulina; lipidomika; Freeze Drying